2021
DOI: 10.1038/s41587-021-00938-z
|View full text |Cite|
|
Sign up to set email alerts
|

Efficient C•G-to-G•C base editors developed using CRISPRi screens, target-library analysis, and machine learning

Abstract: Development of a set of C•G-to-G•C transversion base editors from CRISPRi screens, targetlibrary analysis, and machine learningThe MIT Faculty has made this article openly available. Please share how this access benefits you. Your story matters. CitationKoblan, Luke W. et al. "Development of a set of C•G-to-G•C transversion base editors from CRISPRi screens, target-library analysis, and machine learning." Nature Biotechnology (June 2021): dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(87 citation statements)
references
References 43 publications
2
73
0
Order By: Relevance
“…It might be possible to resolve the mechanism through mining a large editing data set. While we were preparing this manuscript, a recent study reported a similar phenomenon in human cells (Koblan et al, 2021). The authors only observed moderately improved C-to-G editing efficiency after replacing the E. coli UNG with a UNG ortholog from Mycobacterium smegmatis (UdgX).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…It might be possible to resolve the mechanism through mining a large editing data set. While we were preparing this manuscript, a recent study reported a similar phenomenon in human cells (Koblan et al, 2021). The authors only observed moderately improved C-to-G editing efficiency after replacing the E. coli UNG with a UNG ortholog from Mycobacterium smegmatis (UdgX).…”
Section: Discussionmentioning
confidence: 67%
“…Interestingly, no single CGBE outperformed other CGBEs at all target sites, echoing our findings in plants. The authors ended up using machine learning to develop a program termed CGBE-Hive for predicting the performance of individual CGBEs based on a large amount of editing data generated in human cells ( Koblan et al, 2021 ). Thus, it is envisioned that a similar approach in plants may be needed for understanding the editing preference of CGBEs in plants to advance the use of C-to-G editing and improve reliability to aid basic and applied plant research.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence identity was important for several unintended substitutions as well (Figure S1I). In particular, C to G transversions by cytosine editors increased over 4-fold at the TCT motif, and were more frequent when the C was followed by a T. This effect was recently used to develop C to G editors elsewhere [32][33][34]. Furthermore, there is evidence that the cytosine base editors also operate on the opposite strand, as G to A edits were found in much greater quantity in cytosine editors than in controls with only wild-type Cas9 (Figure 1C), and these edits also mirrored motif preferences, albeit with lesser effect on the opposite strand (300% increase in TC to TT in BE4, 50% increase in GA to AA).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, due to the relatively high prevalence of false-negatives with the technology, especially in negative-selection screens, the benefit of added depth is worthwhile, enabling the use of multiple unique guides to pinpoint regions of particular interest in a target locus. The recent development of a nearly-PAM-less Cas9 variant 26 , as well as approaches to generate C>G edits 5255 , suggests that more editing outcomes and thus even finer resolution will be possible for base editor screens. Generating a library of every possible amino acid substitution for an entire open reading frame is certainly possible 5658 , but is also expensive.…”
Section: Discussionmentioning
confidence: 99%